ASSESSMENT OF THE PROFESSIONAL COMPETENCE OF A RURAL SCHOOL TEACHER - Irina M. Zakharova; Lilia R. Sadykova; Nailya G. Khakimova, (Russian Journal of Education and Psychology, 2022)
The purpose of the work is to summarize the results of a pilot study of the assessment of the structural components of the professional competence of a rural school teacher, to determine the principles and directions of research on the design of a diagnostic map for assessing the professional deficits of a teacher working in a rural school.